Identification of Optimal Reference Genes for Expression Analysis in Radish (Raphanus sativus L.) and Its Relatives Based on Expression Stability - Duan, Mengmeng; Wang, Jinglei; Zhang, Xiaohui; Yang, Haohui; Wang, Haiping; Qiu, Yang; Song, Jiangping; Guo, Yangdong; Li, Xixiang (Frontiers in Plant Science, 2017)
Radish (Raphanus sativus) is an important cruciferous root crop with a close relationship to Chinese cabbage (Brassica rapa). RT-qPCR is used extensively to evaluate the expression levels of target genes, and accurate measurement of target gene expression with this method is determined by the valid reference genes used for data nomalization in different experimental conditions. Screening for appropriate reference genes with stable expression based on RT-qPCR data is important for gene expression and functional analysis research in radish and its relatives. However, many researches have thought that almost no single reference gene is widely suitable for all experimental conditions, and few researchers have paid attention to the validation of reference genes in radish gene expression analysis. In the present study, 12 candidate reference genes were selected for analysis. Their expression in 28 samples, including 20 radish samples from different organs and conditions, four Chinese cabbage organs and four organs of their distant hybrid, was assessed by RT-qPCR and then five software tools—ΔCt, geNorm, NormFinder, BestKeeper and RefFinder—were used to compare their expression stability. The results showed that the most suitable reference genes were different in different organs and conditions. GAPDH, DSS1 and UP2 were optimal reference genes for gene expression analysis in all organs and conditions in radish. UPR, GSNOR1 and ACTIN2/7 were the most stable reference genes in different radish organs. UP2 and GAPDH were suitable reference genes for radish pistil development studies. RPII, UBC9 and GAPDH had the most stable expression in radish under various stresses. DSS1, UP2 and TEF2 were the optimal reference genes for Chinese cabbage organs, whereas TUA was optimal for the distant hybrid. UP2, GAPDH and TEF2 were appropriate reference genes for all of the samples together. The optimal reference genes we identified, UP2, GAPDH, UPR and GSNOR1 were verified by normalizing the expression patterns of YAB3, RPL and FUL. These results will provide important information for selecting target reference genes in different research contexts and improve the accuracy and precision of gene expression analysis for radish, Chinese cabbage and their distant hybrid.